2013
DOI: 10.1080/00207594.2013.806811
|View full text |Cite
|
Sign up to set email alerts
|

Family routines and rituals in the context of chronic conditions: A review

Abstract: This paper is a systematic review of 39 empirical studies on family routines and rituals in the context of a chronic condition of a family member. The search strategy encompassed a wide spectrum of chronic conditions affecting family members from childhood/adolescence to adulthood. Twenty quantitative, 13 qualitative, 3 mixed-methods, and 3 intervention studies published between 1995 and 2012 were reviewed. A conceptual framework of routines and rituals as key elements of family health was adopted, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 62 publications
(133 reference statements)
3
70
0
9
Order By: Relevance
“…They also must elaborate care plans directed to families of patients, who are a source of support and help for those with a chronic conditions. (7,20) In this perspective, a study carried out in Nigeria among 2,000 individuals with hypertension showed that the most common source of medical information for approximately 60.0% of interviewers were members of the family, friends and social group of trust; physicians, nurses and other health workers were mentioned as the main providers of information and knowledge about the disease and its treatment for only about 9.0% of individuals. (21) A meta-analysis including controlled studies from China showed that health education with family support -the most commonly used intervention -were, in general, an indispensable component of patient self-management and a trigger for better control of hypertension and, in turn, better quality of life with the disease and its treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also must elaborate care plans directed to families of patients, who are a source of support and help for those with a chronic conditions. (7,20) In this perspective, a study carried out in Nigeria among 2,000 individuals with hypertension showed that the most common source of medical information for approximately 60.0% of interviewers were members of the family, friends and social group of trust; physicians, nurses and other health workers were mentioned as the main providers of information and knowledge about the disease and its treatment for only about 9.0% of individuals. (21) A meta-analysis including controlled studies from China showed that health education with family support -the most commonly used intervention -were, in general, an indispensable component of patient self-management and a trigger for better control of hypertension and, in turn, better quality of life with the disease and its treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that family experience is directly related to confrontation of chronic conditions by the individual, we emphasize that insertion of family in care planning and its implementation can contribute to improve control from the perspective of a sick individual, and also how the disease and management of treatment are significant and experienced in terms of the family dynamics. (7) Therefore, we highlight, on the basis of the literature, that motivation linked to individuals changing can work better when it is based on a plan of goals for self-care, especially when health professionals act as partners for elaboration, accompanying and supporting a plan to solve or reduce barriers experienced by individuals with chronic conditions. (8) In addition, we presuppose that elaboration of care plans can result in differences in care for those with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Quite often the healthy siblings do not outwardly express their suffering; one can hardly confess his suffering to his parents if they're never around. Of course these parents are frequently absent from home because they are with doctors or at the hospital with their sick child, so they are victims of their own feelings [10].…”
Section: Siblings Facing Illnessmentioning
confidence: 99%
“…This way, it is up to the student to focus his training on a biopsychosocial model centered on a multiprofessional team to execute an efficient care plan. 13 The application of instruments of family approach was of great importance to increase the knowledge and validate it as a resource in the bond with patient -his family, friends, relationships with people and with the community, with his religion and with the FHU.…”
mentioning
confidence: 99%